2021
DOI: 10.1007/s13312-021-2290-7
|View full text |Cite
|
Sign up to set email alerts
|

Competency-Based Assessment in Pediatrics for the New Undergraduate Curriculum

Abstract: Medical Council of India (MCI) implemented competency-based curriculum for undergraduate medical education nationwide in 2019, with assessment of competencies being its integral component. The curriculum has outlined some broad principles and components of assessment, but the process and schedule for formative and summative assessment is to be decided by the universities and institutions. In this document, we summarize the recommendations for the subject of Pediatrics, and propose an assessment model for summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…There appears to be insufficient human capacity in research as well as few research mentors and role models, and a lack of a research culture, which can have a negative impact on research output in HPE institutions in lowincome countries. Thus, although there is a significant Table 3 Assessment models, frameworks, type, approach and methods and study sample [23][24][25][26][27][28][29][31][32][33][34][35] NB: Grey scale sections were not reported amount of innovation taking place in HPE institutions in LMICs, there is still limited research output. There also seems to be insufficient networking among research communities in LMICs, meaning that support among researchers is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There appears to be insufficient human capacity in research as well as few research mentors and role models, and a lack of a research culture, which can have a negative impact on research output in HPE institutions in lowincome countries. Thus, although there is a significant Table 3 Assessment models, frameworks, type, approach and methods and study sample [23][24][25][26][27][28][29][31][32][33][34][35] NB: Grey scale sections were not reported amount of innovation taking place in HPE institutions in LMICs, there is still limited research output. There also seems to be insufficient networking among research communities in LMICs, meaning that support among researchers is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This stagnation could be linked to the curriculum innovation taking place within many HPE institutions, which means that they are yet to establish feasible assessment approaches in their contexts. To illustrate this point, half of the papers (n = 7) from the review reported on the development of, or proposals to develop assessment models, which are thus yet to be implemented [29][30][31][32][33][34][35]. HPE institutions still seem to be trying to find their footing in terms of assessment in CBE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation